Innovative business model as a source of competitive advantage for high-tech markets - Demkiv, Yaryna (Видавництво Львівської політехніки, 2013)
The role of innovative business model application for company's succesfull innovation activity is examined. The meaning of business model and innovative business model are defined. Components necessary to successful innovative business model are singled out. The nessesary conditions for innovative business model implementation success are described.
Keywords: innovation; business model; high technologies; value; commercial implementation